THE ROLE OF SENIOR PEERS IN STUDENTS’ TRANSITION TO CLINICAL CLERKSHIPS - Dian Puspita Sari; Yoga Pamungkas Susani (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2018)
Background: Medical students’ transition to clinical clerkship has been shown to be challenging. Students need to effectively adjust to the new learning environment. This study aims to explore the role of senior peers in students’ experiences during transition to clinical clerkships.Methods: A qualitative methodology was adopted for this study. Eight 4th year medical students (5 female, 3 male) submitted audio diaries during their first 12 weeks of clinical clerkships. 73 audio diaries were collected in total. Data were analyzed thematically. Twenty-five out of the 73 audio diaries contained interactions with senior peer students and these interactions were captured in 38 excerpts. These excerpts were analyzed further to understand the role of senior peer students during the transition.Results: Senior peer students helped to ease out transition to clinical clerkship by serving three roles: (1) transferring information on ways of working in a clinical environment, on social aspects of clinical environments and on learning issues; (2) providing exemplars in performing clinical tasks as well as learning tasks; (3) as co-workers who provided access and support students’ participation. Conclusions: Senior peer students in a clinical clerkship helped newcomers to navigate themselves in a clinical environment by helping them to build situational awareness, by supporting vicarious learning and supporting students’ participation in a clinical environment.